The Age of Uncertainty, Organization, and Chaos Theory - Gallardo Velázquez, Anahí (Administración y Organizaciones, 2025)
Over the born of the XXI century, in front of a growing complex, changing, and uncertain world, favored by technological advances in information and telecommunications, chaos and paradoxes are present at any level on the human knowledge scale. They defy learned paradigms because no explanation seems to express the facts but generates new theoretical perspectives to express them as a better comprehension of reality. Caos, complexity, and uncertainty may explain, in different ways, such a transforming organization.